Integrating civilian agencies in stability operations - Szayna, Thomas S., 1960- (Rand Corporation monograph series., 2009)
RAND Arroyo Center examined the question of how the Army can help make key civilian agencies more capable partners in the planning and execution of stability, security, transition, and reconstruction (SSTR) operations. The authors identify the primary and secondary civilian agencies that should be involved in strategic-level planning and implementation of SSTR operations. Then, relying on available information on Provincial Reconstruction Teams and using a variety of federal databases, the authors identify the skill sets needed for the envisioned Field Advance Civilian Teams and where these skills reside in the federal government. The authors then assess the capacity of the main civilian agencies to participate in SSTR operations and analyze the recurring structural problems that have plagued their attempts to do so. The authors suggest a series of options that are worth considering in order to improve the current situation. Even without much action at the national level, the Army can still improve the situation by improving Army Civil Affairs and by executing a well-thought-out strategy of liaison officers assigned to the civilian agencies most important for SSTR operations.